Manajemen Pelayanan Terpadu Satu Pintu (PTSP) dalam Meningkatkan Kualitas Layanan Pendidikan di MAN 2 Kulon Progo - Susana Widyawati; Rahmat Mulyono; Jumintono; Semiono Raharjo (JURNAL ARMADA PENDIDIKAN, 2026)
This study analyzes the implementation of One Stop Integrated Service (PTSP) management at MAN 2 Kulon Progo, a madrasah with the Integrity Zone (ZI) and Corruption Free Area (WBK) status. This study describes the implementation of the POAC function, identifies supporting and inhibiting factors, and formulates improvement strategies. This study uses a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The main data sources for this study were the madrasah principal, PTSP officers, and service users, while data analysis was conducted using the interactive model from Miles and Huberman. The results show that PTSP management has been carried out systematically, starting with thorough SOP-based planning and then executed through a clear organizational structure. This consistent and responsive service implementation is monitored through a continuous control mechanism, ensuring the achievement of quality standards. The main supporting factors include leadership commitment and ZI/WBK status, while inhibiting factors include limited digital infrastructure and human resource capacity. It was concluded that PTSP management significantly improved the quality of educational services, as evidenced by the very high level of community satisfaction (SKM), while also confirming the success of the madrasah in implementing its commitment as an Integrity Zone and Corruption Free Area.